Changes in incidence rates of retinopathy of prematurity in Odessa region in the years of 2009 to 2016 - S.V. Katsan; E.S. Zaichko (Ukrainian Society of Ophthalmologists, 2017)
Background. Although retinopathy of prematurity (ROP) is a wide-spread disease, statistical data are absent; so studying the incidence of ROP in Ukraine is of importance. Purpose. To study the incidence of retinopathy of prematurity in Odessa oblast (region) in children whose birth weights were < 2500 g. Material and Methods. We followed up 2682 premature babies. The initial examination was performed at four to six weeks after children's birth. The examination included ophthalmoscopy under medical mydriasis using a binocular forehead ophthalmoscope with aspheric lenses of 20 and 30 D. The examination findings were registered according to recommendations of the International Committee for Retinopathy of Prematurity and following the International Classification of Retinopathy of Prematurity (ICROP). Analysis was processed using softwares MedCalc v.16.8.4 (MedCalc SoftWare bvba, 1993-2016) and MedStat (Lyakh Yu.E., Gurianov V.G. 2004 - 2011). Results. The mean values for the period of 2009-2016 were 24.7% (95% CI: 18.2- 31.7%) for ROP incidence rates; 19.4% (95% CI: 13.6-25.9%) for stage 1-2 ROP; 4.9% (95% CI: 3.3-6.8%) for ROP cases requiring laser treatment. The stage 1-2 ROP incidence was 47.6% and 87.9% in 2009 and 2016, respectively (p<0.001 according to the Chi-squared test for the presence of the trend for the ordered categories). Conclusions. The incidence of retinopathy of prematurity increased in Odessa Oblast from 10% in 2009 to 27% in 2016. The incidence of stage 1-2 ROP increased from 4.7 % in 2009 to 23.8 % in 2016. The incidence of stage 3 ROP decreased to 2.3% in 2016 vs. 5.2% in 2009. In 2016, aggressive posterior ROP was diagnosed in 1.0 % of cases. The frequency of laser treatment decreased to 3.3% in 2016 compared to 5.2% in 2009.